(untitled) (Semiárida, 2018)
Pork is the meat of major consumption in the world, and changes in consumer’s profile and eating patterns guide the evolution of pig production sector. The objective of this work was to characterize the consumption of pork in Santa Rosa, La Pampa by means of a semi-structured survey involving consumers of fresh pork. The growing of pork consumption in recent years was the result of an increase in number of consumers. The consumer’s choice for pork was driven by taste, and loin steak was the most chosen cut consumed. The most frequent consumption routine had a monthly pattern, while grilled was the predominant way of pork preparation. Ignorance and prejudice were important preventing the growth of pork inclusion in the diet of Santa Rosa households. It was ascertained that knowledge about cuts is essential to promote pork consumption through specific marketing strategies. Tactics on price, product, location and promotion are suggested to plan a proper development of the provincial swine chain, with basis on demand increase, in order to achieve a sustainable positioning. Besides, strategies are proposed involving the design of appropriate public policies that address the information obtained in the present study.